Inhibition of angiogenesis induced by cerebral arteriovenous malformations using Gamma Knife irradiation - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2007)
Object. The authors studied the effect of Gamma Knife irradiation on angiogenesis induced by cerebral arteriovenous malformation (AVM) tissues implanted in the corneas of rats. Methods. Ten AVM specimens obtained from tissue resections performed at Marmara University between 1998 and 2004 were used. A uniform amount of tissue was implanted into the micropocket between the two epithelial layers of the comea. Gamma Knife irradiation was applied with dose prescriptions of 15 or 30 Gy to one comea at 100% isodose. Dosing was adjusted so that the implanted cornea of one eye received 1.5 Gy when 15 Gy was applied to the other comea. Similarly, one cornea received 3 Gy when 30 Gy was applied to the other cornea. Angiogenic activity was graded daily by biomicroscopic observations. Forty-eight other rats were used for microvessel counting and vascular-endothelial growth factor (VEGF) staining portions of the experiment. Micropieces of the specimens were again used for corneal were killed on Days 5, 10, 15, and 20, and four corneas from each group were examined. Gamma Knife irradiation dose dependently decreased AVM-induced neovascularization in the rat cornea as determined by biomicroscopic grading of angiogenesis, microvessel count, and VEGF expression. Conclusions. The results suggest that Gamma Knife irradiation inhibits angiogenesis induced by AVM tissue in the cornea angiogenesis model. The data are not directly related to understanding how Gamma Knife irradiation occludes existing AVM vasculature, but to understanding why properly treated AVMs do not recur and do not show neovascularization after Gamma Knife irradiation.
Keywords: angiogenesis; arteriovenous malformation; Gamma Knife surgery; irradiation; vascularendothelial growth factor; ENDOTHELIAL GROWTH-FACTOR; STRUCTURAL PROTEINS; EXPRESSION; RECURRENCE; BRAIN; RADIOSURGERY; OBLITERATION; MECHANISMS; INTEGRINS; ADULT